Draft Annual Plan 1984-85 (Brief Memorandum Along with G.N. and Other Statement) Haryana State - Planning Commission (Planning Commission, 1983)
House sites in rural areas have been provided to 2.45lacs families up to 1982-83. The anticipated achievement for 1983-84 is 50,000. This will leave a balance of about 27,000 eligible families which will be provided house sites during 1984-85. In the field of Irrigation the target for Sixth Plan was for creation of an additional potential of 5.18 lakh hectares. During the first three years the additional potential created was 2.22 lakh, hectares, the anticipated achievement during 1983-84 is 0.65 lakh hectares and target for 1984-85 is 0.72 lakh hectares. Thus by the end of Sixth Plan the achievement will be 3.59 lakh hectares. The shortfall in achieving the target is only due to non-completion of SYL Canal. In the field of Power against the Sixth Plan target of 571 MW of additional generation capacity, the likely achievement is 649 MW out of which 195 MW is expected to be share from Central Sector. Piped Water Supply had been arranged in 2135 problem villages up to 1982-83. The anticipated achievement during 1983-84 is 415 and target for 1984-85 is 472 including 72 under ARP. Thus by the end of Sixth Plan 3022 villages out of 4690 problem villages will be covered.
Planning Department, Government of Haryana